(untitled) (Research, Society and Development, 2022)
Objective: To analyze the instructional technology in the context of the quality of life of caregivers of elderly people with Parkinson’s disease. Method: the study is an integrative literature review based on the guiding question "what is the importance of instructional technology in the quality of life of caregivers of elderly people affected by Parkinson’s disease?". These searches started in October 2021 and went on until December 2021, whose bases consulted were: Medline, Scielo, Lilacs, Institutional Repository/UFSC, E-Publicações/UERJ, Portal de Periódicos - CAPES, IBECS, using the following keywords: "health of the elderly", "health education", "instructional technology", "educational technology" and "caregivers" with the use of some Boolean (AND). The sample was based on 28 studies selected for analysis, which ranged from 2015 to 2021 in the languages of Portuguese and English related to Caregivers of Parkinson’s Disease and Health Technologies. Results: Of the 28 studies selected, 13 contributed to the analysis on strategies for improving self-care of caregivers of older adults with Parkinson’s Disease with instructional technologies. Historical and conceptual data on instructional technologies could also be identified. Conclusion: The studies selected in this integrative review evidenced the effects of instructional technologies on caregivers’ perception of their needs, both in terms of difficulties and interests. Several researches proved experimental studies that tested positive effects of this technology.